Decreased prevalence of asymptomatic choroidal metastasis in disseminated breast and lung cancer: argument against screening - Barak, A (BMJ Group, 2007)
AIM: To determine the frequency of visually asymptomatic choroidal metastases in patients with disseminated breast and lung carcinomas in order to establish optimal patient management policies. METHODS: All patients with confirmed metastatic disease treated in our institution between January 2002 and December 2003 were invited to undergo a funduscopic examination and a B‐scan ultrasound evaluation. RESULTS: Of the 169 study participants, 77 had breast cancer (64 with metastases in one organ and 13 with multiple‐organ involvement) and 92 had lung cancer (85 with metastases in one organ and 7 with multiple‐organ involvement). No patient with metastatic breast cancer and two patients with metastatic lung disease (each with multiple‐organ involvement) were found to have choroidal metastases. The choroidal metastases were detected by both the funduscopic and ultrasound examinations. CONCLUSIONS: The 2.17% incidence of choroidal metastasis in disseminated lung cancer and the 0% incidence in disseminated breast cancer speaks against the practicality of screening for early detection of choroidal metastasis among these patients, even though it would lead to early implementation of appropriate, often vision saving, therapeutic management. Its low incidence probably testifies to progress achieved by enhanced systemic oncological treatment policies that have been introduced into routine patient management over the past few years.